Proposed Convict Enfranchisement in the Gambia: Lessons from America - Akpojevbe Omasanjuwa (Journal of Universal History Studies)
Convict enfranchisement is among the themes The Gambia Constitution Review Commission is addressing in its appraisal and updating of the 1997 constitution. The dawn of a new political dispensation necessitated the assignment to usher in a third republic. By means of the United States case law, a country where most felonies lead to disenfranchisement, this article examine the likely consequences of enfranchising convicts in The Gambia. Blalock’s Group Threat hypothesis explained the ulterior motives fuelling the enfranchisement call as the social dynamics of the country contrasts those of other nations like the United States which The Gambia seems to be keeping up with. Rather than addressing the issue of enfranchising an insignificant number of convicts, the conclusion shows that tackling constitutional irrationalities undermining the principles propping the separation of powers will be more beneficial.